Guide to state politics and policy - Niemi, Richard G.; Dyck, Joshua J. (CQ Press, an Imprint of SAGE Publications, 2014)
This guide provides up-to-date coverage of state government and politics, along with the states' current and future public policies. It includes contemporary analysis of state institutions, processes, and public policies, along with both historical and theoretical perspectives that help readers develop a comprehensive understanding of the 50 U.S. states' complex and changing political spheres.